2006
DOI: 10.1159/000090495
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Enhancing Role of Vitamin C and Zinc and Effect on Clinical Conditions

Abstract: Vitamin C concentrations in the plasma and leukocytes rapidly decline during infections and stress. Supplementation of vitamin C was found to improve components of the human immune system such as antimicrobial and natural killer cell activities, lymphocyte proliferation, chemotaxis, and delayed-type hypersensitivity. Vitamin C contributes to maintaining the redox integrity of cells and thereby protects them against reactive oxygen species generated during the respiratory burst and in the inflammatory response.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
303
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(315 citation statements)
references
References 132 publications
1
303
0
11
Order By: Relevance
“…Further, it has been shown that AA blocks pathways that lead to apoptosis of T-cells and thus stimulate or maintain T-cell proliferation to attack the infection. This mechanism has been proposed for the enhanced immune response observed after administration of vitamin C during rhinitis [36,37].…”
Section: Vitamin C and Common Coldmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, it has been shown that AA blocks pathways that lead to apoptosis of T-cells and thus stimulate or maintain T-cell proliferation to attack the infection. This mechanism has been proposed for the enhanced immune response observed after administration of vitamin C during rhinitis [36,37].…”
Section: Vitamin C and Common Coldmentioning
confidence: 95%
“…Supplementation of vitamin C has been shown to improve components of the human immune system such as antimicrobial and NK cell activities, lymphocyte proliferation, chemotaxis, and delayed-type hypersensitivity as discussed above. Vitamin C contributes in maintenance of the redox integrity of cells and thereby protects them against ROS generated during the respiratory burst and in the inflammatory response [197].…”
Section: Vitamin C and Immunitymentioning
confidence: 99%
“…Supplementation of vitamin C was found to improve components of the human immune system such as antimicrobial and natural killer cell activities, lymphocyte proliferation, chemotaxis, and delayed-type hypersensitivity. Several cells of the immune system can indeed accumulate vitamin C and need the vitamin to perform their task, especially phagocytes and t-cells [60]. Thus a vitamin C deficiency results in a reduced resistance against certain pathogens whilst a higher supply enhances several immune system parameters.…”
mentioning
confidence: 99%
“…Esta vitamina e os leucócitos rapidamente declinam durante as infecções e o estresse. Outros observaram que o aumento da concentração plasmática de vitamina C era associado à melhora dos componentes do sistema imunológico, tais como, a atividade antimicrobiana e das células natural killer, a proliferação de linfócitos e a quimiotaxia 19 . A vitamina C e os linfócitos destas mulheres estavam em concentrações consideradas deficientes, o que poderia contribuir para piora das defesas imunológicas e da neutralização da produção de radicais livres.…”
Section: I S C U S S ã Ounclassified